Keanekaragaman Tumbuhan Jenis Asing Invasif di Sepanjang Jalan Pertamina Komplek Patra Asri, Kota Bandung Jawa Barat - Anna Hygia Fitrianti; Savira Puji Lestari; Rahmat Taufiq Mustahiq Akbar (Politeknik Kampar, 2023)
Invasive foreign species (JAI) are the most serious problem for ecosystems and biodiversity, especially in protected areas. Its fast and aggressive growth makes it easy for it to dominate the land. Tight competition for water, light and nutrients is a serious problem. Therefore, the aim of the research carried out along the Pertamina Complex Patra Asri road, Bandung City, is to determine the diversity of invasive foreign plant species found along the Pertamina road, Patra Asri Complex. The research method was carried out by collecting data directly. Invasive foreign plant species found in the category of spreading to other trees are Mikania micrantha and Ipomoea Cairica. The other types are Mimosa pigra, Imperata cylindrica, Bidens Pilosa L., Paspalum distichum L., and Sesbania drummondii. The impact of invasive plants spreading on other plants will reduce and threaten local growth. Invasive plants can also harm local plants in terms of physiology and morphology as they try to defend and compete for nutrients with invasive plants. Environmental damage due to invasive plants will result in physical damage to the habitat, such as blocking waterways, damaging building structures and disturbing beauty.